Emerging pharmaceuticals and industrial chemicals in Nakdong River, Korea: Identification, quantitative monitoring, and prioritization. (January 2021) - Park, Naree; Jeon, Junho
Abstract: The extensive development and use of new anthropogenic chemicals have inevitably led to their presence in aquatic environments. Surface waters affected by sewage effluents have been exposed to these new substances. In the present study, the occurrence of anthropogenic substances, including pharmaceuticals and industrial chemicals, was investigated in one of the major rivers in Korea, the Nakdong River. Furthermore, seasonal variations in their content were determined via annual monitoring. Through the suspect and non-target screening (SNTS) technique, 58 substances were newly identified in the river and integrated in the quantitative monitoring practice. The results revealed that niflumic acid and melamine exhibited the highest median concentrations, i.e., 320 ng/L and 11, 000 ng/L, respectively. The results associated with seasonal change revealed that the concentration of a considerable number of substances increased in winter when the flow rate was low. Conversely, some substances exhibited high concentrations in summer (e.g., polyethylene glycol) and spring (e.g., niflumic acid). This was attributed to the seasonal changes in the consumption, prescriptions, or the application of alternative substances. These changes were also reflected by the risk quotient (RQ) values calculated from the concentration and toxicity values. Pharmaceuticals such as telmisartan and carbamazepine and industrial chemicals such as organophosphorus flame retardants (OPFRs) and melamine accounted for approximately 90% of the total RQ. Major substances prioritized using the production of the RQ value and the detection frequency included OPFRs and telmisartan. It is recommended that these results be reflected in future water quality monitoring plans. Graphical abstract: Image 1 Highlights: Suspect and non-target screening identified 36 emerging substances in Nakdong River. Seventy-two substances were quantified via year-round monitoring. Melamine showed the most overwhelming concentration, up to 94, 100 ng/L. Niflumic acid was a major pharmaceutical with maximum concentration of 767 ng/L. OPFR, telmisartan and melamine were prioritized due to their high RQ values.